Casein kinase 1 epsilon facilitates cartilage destruction in osteoarthritis through JNK pathway. Issue 5 (16th March 2020) - He, Tianwei; Wu, Depeng; He, Lei; Wang, Xuan; Yang, Bu; Li, Shangfu; Chen, Yuyong; Wang, Kun; Chen, Ruiqiang; Liu, Bin; Zhang, Liangming; Rong, Limin
Abstract: Osteoarthritis (OA) is a high‐morbidity skeletal disease worldwide and the exact mechanisms underlying OA pathogenesis are not fully understood. Casein kinase 1 epsilon (CK1ε) is a serine/threonine protein kinase, but its relationship with OA is still unknown. We demonstrated that CK1ε was upregulated in articular cartilage of human patients with OA and mice with experimentally induced OA. Activity of CK1ε, demonstrated by analysis of phosphorylated substrates, was significantly elevated in interleukin (IL)‐1β‐induced OA‐mimicking chondrocytes. CK1ε inhibitor or CK1ε short hairpin RNA (shRNA) partially blocked matrix metalloproteinase (MMP) expression by primary chondrocytes induced by IL‐1β, and also inhibited cartilage destruction in knee joints of experimental OA model mice. Conversely, overexpression of CK1ε promoted chondrocyte catabolism. Previous studies indicated that CK1ε was involved in canonical Wnt/β‐catenin signaling and noncanonical Wnt/c‐Jun N‐terminal kinase (JNK) signaling pathway. Interestingly, the activity of JNK but not β‐catenin decreased after CK1ε knockdown in IL‐1β‐treated chondrocytes in vitro, and JNK inhibition reduced MMP expression in chondrocytes overexpressing CK1ε, which illustrated that CK1ε‐mediated OA was based on JNK pathway. In conclusion, our results demonstrate that CK1ε promotes OA development, and inhibition of CK1ε could be a potential strategy for OA treatment in the future.